PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEAD TUGETHER (NHT) UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS V SDN 6 KADUR - Nazaruddin Nazaruddin; Lazim N Lazim N; Zairul Antosa (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The problem of this research is the low of IPS student learning result, it can be seen from the average score of student that is 69,34 (from 23 students reaching KKM only 10 students (43.48%) while students who have not reached KKM 13 students, the value of KKM is 70. Based on the problem, it is necessary to research the class action by applying the model of cooperative learning type of Numbered Head Together (NHT) .The research aimed to improve the learning outcomes of IPS students of grade V SD Negeri 6 Kadur Lesson Year 2016 / 2017 with the number of students as many as 23 students.The student learning activity at each meeting, from 44.83% at the first meeting Cycle I to 62.50% in the second meeting of cycle I, then increased again to 79.16% at the first meeting of cycle II into 83,33% while teacher activity at first meeting of cycle I from 66,66% to 75,00% at second meeting of cycle I, then at first meeting ama cycle II from 79.16% to 87.5% in the second meeting of cycle II.Peningkatan learning outcomes from the basic score to UH1 that is from an average of 69.34 to 75.43 with an increase of 8.78% and then increase learning outcomes from the basic score to UH2 is from an average of 69.34 to 85.0 with a percentage increase of 18.20% From the results of this action analysis supports the proposed hypothesis that if applied cooperative learning model type Numbered Head Together (NHT) then it can increase the results of learning IPS students Class V SD Negeri 6 Kadur.Keywords: Cooperative learning model of NHT type, IPS learning result